2017
DOI: 10.15446/rev.colomb.biote.v19n2.70429
|View full text |Cite
|
Sign up to set email alerts
|

Utilización de microalgas de la división Chlorophyta en el tratamiento biológico de drenajes ácidos de minas de carbón

Abstract: El impacto ambiental generado por las aguas residuales de la explotación de carbón es significativo por la carga contaminante que estas por lo general poseen, representada en grandes concentraciones de sólidos suspendidos, metales (principalmente hierro) y otros elementos traza, además del bajo pH que suelen tener. El objetivo del presente trabajo fue evaluar la eficiencia de un sistema de tratamiento biológico a partir de microalgas de la división Chlorophyta para remover la carga contaminante de las aguas re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Overall, the results of this experiment are similar to that reported by Torres et al, (Torres et al 2017), where they obtained removal e ciencies of 66% for total Fe in a treatment system with microalgae from the Chlorophyta division to remove the pollutant load of sewage from a coal mine. Also, (Abdel-Razek et al 2019), evaluated the use of pure cultures of Chlorella vulgaris, Scenedesmus quadricuda, and Spirulina platensis to eliminate Cd, Ni, and Pb from urban and agricultural wastewater.…”
Section: General Performancesupporting
confidence: 89%
“…Overall, the results of this experiment are similar to that reported by Torres et al, (Torres et al 2017), where they obtained removal e ciencies of 66% for total Fe in a treatment system with microalgae from the Chlorophyta division to remove the pollutant load of sewage from a coal mine. Also, (Abdel-Razek et al 2019), evaluated the use of pure cultures of Chlorella vulgaris, Scenedesmus quadricuda, and Spirulina platensis to eliminate Cd, Ni, and Pb from urban and agricultural wastewater.…”
Section: General Performancesupporting
confidence: 89%
“…In Colombia, there are few studies focused on the use of microalgae in food, animal production, and agriculture, despite the enormous potential of its biodiversity, water resources, climate, as well as the fulfilling needs driven by the high rates of poverty and malnutrition in the country [7]. In contrast, research in Colombia is mainly focused on the use of microalgae in the production of total lipids for biodiesel, wastewater treatment, and bioremediation [119][120][121][122][123][124]. Some research has recently begun in the agro-alimentary sector; however, little has been implemented in recent years (Table 1).…”
Section: Microalgae Production In Colombiamentioning
confidence: 99%
“…Microalgae have the metabolic capacity to remove iron and heavy metal compounds (22) . It has been reported that for microalgae to carry out this process, they follow two mechanisms: absorption (active/passive) and adsorption, mainly through physical adsorption, chemical adsorption and chelation (33) .…”
Section: Kinetic Parameters Estimation and Nutrient Removalmentioning
confidence: 99%
“…This problem is caused by mines that do not treat MAD, given the high cost of treating these effluents, as well as the lack of technologies that take advantage of these effluents so they could be reincorporated into the process. Some authors have reported the potential of microalgae to grow using MAD, although there is still not much work in this area (22) Therefore, the objective of this Source: own elaboration work is to evaluate the effect of three different nitrogen sources under autotrophic and mixotrophic conditions using DAM, generated in a mine in northeastern Colombia, to determine if there is an effect on the production of biomass and carotenoids using Scenedesmus sp.…”
Section: Introductionmentioning
confidence: 99%